2017
DOI: 10.1177/1066480717697688
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Parenting in Australia

Abstract: This study employed a qualitative and social constructionist approach to examine cultural differences in intercultural parenting and how parents negotiated cultural differences. Semistructured, in-depth interviews were conducted with 14 intercultural couples/parents. Thematic analysis was used to analyze data and understand the meanings of participants' experiences. The findings revealed that while intercultural couples experienced several similar aspects of parenting experienced by monocultural couples, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 20 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Participants reported many instances in which they creatively accommodated and blended multiple value systems within their own approach to parenting in Australia. Although 'intercultural parenting' often refers in the literature specifically to parenting in multicultural, multiracial or multifaith households (Bhugun, 2017), we deploy this term intentionally to highlight the many ways in which African parents chose and applied what they perceived as the 'best of both' values systems, thus capturing the spirit of contemporary definitions of 'interculturalism' (Mansouri, 2017). A systematic review of literature by Mugadza, Mujeyi, Stout, Wali and Renzaho (2019) showed that African migrant parenting styles can be generally characterized 'by very high parental expectations of children … imposing obedience and respect for elders with harsh punishment for deviation … and using corporal punishment as a method of discipline ' (p. 2928).…”
Section: Intercultural Parenting-accommodating Multiple Value Systemsmentioning
confidence: 99%
“…Participants reported many instances in which they creatively accommodated and blended multiple value systems within their own approach to parenting in Australia. Although 'intercultural parenting' often refers in the literature specifically to parenting in multicultural, multiracial or multifaith households (Bhugun, 2017), we deploy this term intentionally to highlight the many ways in which African parents chose and applied what they perceived as the 'best of both' values systems, thus capturing the spirit of contemporary definitions of 'interculturalism' (Mansouri, 2017). A systematic review of literature by Mugadza, Mujeyi, Stout, Wali and Renzaho (2019) showed that African migrant parenting styles can be generally characterized 'by very high parental expectations of children … imposing obedience and respect for elders with harsh punishment for deviation … and using corporal punishment as a method of discipline ' (p. 2928).…”
Section: Intercultural Parenting-accommodating Multiple Value Systemsmentioning
confidence: 99%
“…Up to 2018, further samples were drawn to increase the number of immigrants, particularly after large immigration waves. Enlargement samples were added in 2013 and 2015 to cover the immigration of European Union (EU) citizens from Central and Eastern Europe after freedom of movement was implemented in the EU, and in 2016 and 2017 to cover the arrival of refugees from Syria and other Middle Eastern countries (Goebel et al 2019). Moreover, to ensure an appropriate sample size, refreshment samples of the residential population of Germany are collected.…”
Section: Methodsmentioning
confidence: 99%
“…This stage is likely to be more conflict-ridden (Singla and Holm 2012). For instance, more conflicts will appear if the partners' gender role attitudes or religious beliefs diverge (Rodríguez-García 2006;Bhugun 2017). If the relationship continues, a shared identity is developed in the form of joint opinions, which strengthens the bond between partners in the later relationship phases (Singla and Holm 2012).…”
Section: Family Life Course Stagesmentioning
confidence: 99%
See 1 more Smart Citation